Latin American artists of the twentieth century a selection from the exhibition = Artistas latinoamericanos del siglo XX : selecciones de la exposición.
After years of neglect by cultural institutions in the United States and Europe, Latin American art, during the past decade, has been the subject of several large exhibition surveys, as well as represented by retrospectives of individual artists. The present exhibition is in several ways perhaps the most ambitious of these efforts, as it represents the works of more than ninety artists with nearly three hundred works, beginning in 1914, with the first generation of early modernists, and extending to young contemporary artists, including Latino artists working in the United States today.